Rapid diagnostic testing combined with an immediate infectious disease consultation increases the rate of septic intensive care unit patients on targeted antibiotic therapy - Evelyn Kramme; Nadja Käding; Nadja Käding; Tobias Graf; Karolin Schmoll; Heidi Linnen; Katharina Nagel; Esther Grote-Levi; Susanne Hauswaldt; Dennis Nurjadi; Dennis Nurjadi; Jan Rupp; et al. (Frontiers in Cellular and Infection Microbiology)
ObjectivesTo evaluate the impact of rapid diagnostic testing (RDT) combined with immediate infectious disease (ID) consultation on the treatment of septic patients with positive blood cultures in intensive care units in a setting without 24/7 service.MethodsAdult ICU patients in a tertiary care hospital with positive blood cultures were included from January 2019 to December 2020. The control group underwent routine laboratory testing, and for the intervention group, RDT was applied with immediate ID consultation.ResultsIn 77 out of the 91 patients in the intervention group, the pathogen was identified by RDT. Regarding antimicrobial susceptibility testing (AST), genotypic testing (ePlex®) was successful for Gram-positive cocci, but inadequate for Gram-negative rods. Phenotypic resistance testing with the Accelerate PhenoTest® took too long to be successfully integrated into the intervention. Adaptation of empirical antibiotic therapy was recommended for 72.7% of the patients. Adherence to the ID consultation post-RDT results was high at 82.3%. In the control group, adaptation of the initial antibiotic therapy would have been recommended for 81.8% of patients, if the species identification had been available. Overall adherence to the local antibiotic therapy guideline for sepsis was significantly lower in the control than in the intervention group (27.8% versus 89.3%, p<0.001).ConclusionIntegration of an RDT system in the microbiological workflow for septic patients in ICU combined with a standardized ID intervention led to a significantly higher percentage of adequate antimicrobial treatment and greater adherence to local antibiotic therapy recommendations, even in a setting where 24/7 service is not available.